Rendahnya Kesadaran Sivitas Akademika sebagai Tantangan Utama Implementasi Green Campus UIN Maulana Malik Ibrahim Malang - Achmad Zamroni (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy article analyzes the low level of awareness among the academic community at UIN Maulana Malik Ibrahim Malang in supporting the Green Campus, which poses a significant obstacle to the realization of the sustainability vision. This research identifies the main root cause, which stems from the lack of strong leadership commitment to enforcing regulations, which directly leads to the absence of clear sanctions or appreciation and low participation in the integrated waste management program. This paper uses qualitative methods with a descriptive analysis approach and USG analysis as well as William N. Dunn's theory, which results in the finding that regulatory alternatives are the most effective solution to address the root cause directly and quickly. As a recommendation, this article proposes the issuance of a Rector's Regulation that is regulatory and binding, containing obligations, administrative sanctions, and a monitoring mechanism. This policy is expected to serve as a strong foundation for changing behavior, increasing participation, and effectively strengthening UIN Malang's reputation as a leading PTKIN fully committed to sustainability.